2017
DOI: 10.1158/1538-7445.am2017-lb-143
|View full text |Cite
|
Sign up to set email alerts
|

Abstract LB-143: Identification of STAT3-NRF2-hypoxia as a novel reinforcing mechanism for promoting cancer stemness

Abstract: Signal transducer and activator of transcription 3 (STAT3) is a transcription factor constitutively activated in many cancer types, and has been identified as a major mediator of cancer stemness (Li et.al., PNAS 2015). The Nrf2 (nuclear factor erythroid 2 [NF-E2]-related factor 2) is the reactive oxygen species (ROS) sensor and a master regulator of antioxidant gene expression. NRF2 has recently been implicated in contributing to cancer stem cell phenotypes, chemoresistance, and is associated with poor clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…19 In this regard, several studies have reported the possibility of the cross-talk between Nrf2 and STAT3, which leads to the reduction of STAT3 expression, the transcriptional activity of Nrf2, and a decrease in its target gene expression. 20 Here, we also observe increased expression of both Nrf2 and STAT3 in HT-29 cell line and provide evidence for Nrf2 and STAT3 cooperation in colon cancer cells. In this study, the cellular cytotoxicity of stattic and 5-FU was assessed in HT-29 cells.…”
Section: Introductionsupporting
confidence: 72%
“…19 In this regard, several studies have reported the possibility of the cross-talk between Nrf2 and STAT3, which leads to the reduction of STAT3 expression, the transcriptional activity of Nrf2, and a decrease in its target gene expression. 20 Here, we also observe increased expression of both Nrf2 and STAT3 in HT-29 cell line and provide evidence for Nrf2 and STAT3 cooperation in colon cancer cells. In this study, the cellular cytotoxicity of stattic and 5-FU was assessed in HT-29 cells.…”
Section: Introductionsupporting
confidence: 72%